Empathy in a Citizen Deliberation Experiment - Kimmo Grönlund; Kaisa Herne; Maija Setälä (WILEY, 2025)
Despite increased scholarly attention, there is still limited knowledge on how empathy works in democratic deliberation. This article examines the role of empathy in citizen deliberation with the help of a deliberative experiment on immigration. First, a random sample of citizens was surveyed regarding their opinions on immigration. Based on their opinions, they were then divided into a permissive or a non-permissive enclave, and randomly assigned into like-minded or mixed-opinion groups for deliberation. After deliberation, they were surveyed anew. The study analyzes: (a) empathy differences between permissive and non-permissive participants; (b) changes in outgroup empathy toward immigrants as a result of deliberation; and (c) differences in prosocial behavior (i.e., donating to charity). The results show that the permissive respondents had more empathy, especially toward immigrants, than the non-permissive respondents. Among participants, outgroup empathy increased during deliberation. Regarding prosocial behavior, the permissive participants donated more often to charity at the end of the experiment.